2021
DOI: 10.1038/s42004-020-00437-3
|View full text |Cite
|
Sign up to set email alerts
|

Real-time observation of tetrapyrrole binding to an engineered bacterial phytochrome

Abstract: Near-infrared fluorescent proteins (NIR FPs) engineered from bacterial phytochromes are widely used for structural and functional deep-tissue imaging in vivo. To fluoresce, NIR FPs covalently bind a chromophore, such as biliverdin IXa tetrapyrrole. The efficiency of biliverdin binding directly affects the fluorescence properties, rendering understanding of its molecular mechanism of major importance. miRFP proteins constitute a family of bright monomeric NIR FPs that comprise a Per-ARNT-Sim (PAS) and cGMP-spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 56 publications
1
7
0
Order By: Relevance
“…8 nm compared to 40 nm in PCB) of the noncovalent intermediate was also observed in two earlier studies of different bacteriophytochromes with different Cys substitutions. 35,36 In these studys, binding of BV via addition to the terminal C-atom of the vinyl group also afforded only minor absorption shifts compared to the noncovalent form, and the introduction of a second Cys residue led to a seccond thioether formation, saturation of Ring A, and larger spectral blue-shifts in line with the present findings for PCB.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…8 nm compared to 40 nm in PCB) of the noncovalent intermediate was also observed in two earlier studies of different bacteriophytochromes with different Cys substitutions. 35,36 In these studys, binding of BV via addition to the terminal C-atom of the vinyl group also afforded only minor absorption shifts compared to the noncovalent form, and the introduction of a second Cys residue led to a seccond thioether formation, saturation of Ring A, and larger spectral blue-shifts in line with the present findings for PCB.…”
Section: Discussionsupporting
confidence: 86%
“…This finding is important for biotechnological apllication of AmI-g2 in cellular environments, where porphyrins and other small hydrophobic molecules compete with bilins for binding to the apo-proteins. 35,41 Therefore, the rate of the bilin uptake (k 1 ) is an important factor playing into the effective concentration of holo-protein in vivo 42 , and is probably at least one of the reasons why the PCB-binding variant performs better as an optogenetic tool in yeast. 8 We also showed that AmI-g2 has very low photochemical quantum yields in both photoswitching directions compared to other red/green CBCRs, independent of which bilin was used.…”
Section: Discussionmentioning
confidence: 99%
“…The analysis in the current work of several NIR FPs with two cysteine residues Cys PAS and Cys GAF corroborated with earlier studies of individual NIR FPs of this group [8,9], indicates that the quantum yield of their fluorescence is additionally affected by the covalent binding of BV simultaneously with two domains in these proteins, which leads to rigid fixation of the chromophore in their chromophore-binding pocket. It should be noted that, according to the literature, the kinetics of covalent binding of the chromophore depends on the number of cysteine residues in NIR FPs: the rate of covalent attachment of BV to Cys GAF is significantly higher in proteins containing both Cys GAF and Cys PAS [38]. In that work, it has been suggested that as a result of rapid covalent fixation of BV in NIR FPs with two cysteine residues, they avoid the formation of non-fluorescent complexes with protoporphyrin in the cell, which increases their brightness [38].…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that, according to the literature, the kinetics of covalent binding of the chromophore depends on the number of cysteine residues in NIR FPs: the rate of covalent attachment of BV to Cys GAF is significantly higher in proteins containing both Cys GAF and Cys PAS [38]. In that work, it has been suggested that as a result of rapid covalent fixation of BV in NIR FPs with two cysteine residues, they avoid the formation of non-fluorescent complexes with protoporphyrin in the cell, which increases their brightness [38]. Thus, several molecular mechanisms are responsible for the higher brightness of dimeric NIR FPs with two cysteine residues Cys PAS and Cys GAF compared to other BV-containing NIR FPs.…”
Section: Discussionmentioning
confidence: 99%
“…Structural variability of BV results in interesting spectral properties in some of these BV-binding proteins. The spectral properties and protein-BV interaction in Bph are well studied [7][8][9]. The A ring of BV is covalently bonded to Bph, and BV is stabilized in ZZZssa conformation.…”
mentioning
confidence: 99%